Effectiveness of the Completion Bonus Program for Achievement in Adult Education - Mary Ziegler; Olga Ebert (Adult Education Research Conference, 2002)
This study examined use of a cash bonus as an incentive for welfare recipients to make progress in Adult Basic Education programs and pass the GED test. The number of people in sixteen programs who made learning gains appears to have increased after the bonus program was introduced.